Machine learning - Mitchell, Tom M. (Tom Michael) 1951- (McGraw-Hill computer science series, 1997)
Mitchell covers the field of machine learning, the study of algorithms that allow computer programs to automatically improve through experience and that automatically infer general laws from specific data.